New business formation and incumbents' perception of competitive pressure - Javier Changoluisa; Michael Fritsch (Friedrich Schiller University Jena, 2016)
We investigate the relationship between new business formation and the level of competitive pressure perceived by manufacturing incumbent establishments. The perceived pressure of competition is stronger the higher the level of entries in the respective industry. This relationship holds not only for start-ups located in the same region of the incumbent, but also for start-ups across all regions of Germany. The productivity level of an incumbent moderates the extent of the perceived competitive pressure from start-ups. Highly productive incumbents are less threatened by new business formation. Such a moderating effect cannot be found for incumbent size and regional population density.
Keywords: L26; L60; D20; O12; R11; 330; competitive pressure; incumbent firms; manufacturing industries; New business formation; regional competition